On the Optimal Policy for Deterministic and Exponential Polling Systems - Bruno Gaujal; Arie Hordijk; Dinard van der Laan (Tinbergen Institute, 2005)
In this paper, we consider deterministic (both fluid and discrete) polling systems with N queues with infinite buffers and we show how to compute the best polling sequence (minimizing the average total workload). With two queues, the best polling sequence is always periodic when the system is stable and forms a regular sequence. The fraction of time spent by the server in the first queue is highly non continuous in the parameters of the system (arrival rate and service rate) and shows a fractal behavior. Convexity properties are shown in Appendix as well as a generalization of the computations to the stochastic exponential case.
Keywords: C60; C63; C65; 330; Polling systems; regular sequences; multimodularity; optimal control; Scheduling-Verfahren; Warteschlangentheorie; Theorie